Assembly and comparative analysis of the mitochondrial genome of Ceratophyllum demersum L. - Yin, Hang; Dai, Xiaogang (Frontiers in Plant Science, 2025)
Mitochondria are the powerhouse of eukaryotic cells, whose genomes feature unique structural characteristics and evolutionary significance. Ceratophyllum demersum is a widely distributed aquatic plant that holds special position in the aquatic ecosystem. In this study, we assembled the mitochondrial genome (mitogenome) of C. demersum from the PacBio HiFi sequencing data, yielding three complete circular chromosomes of lengths 285,151 bp, 208,195 bp and 101,944 bp. The three molecules contain 65 unique genes comprising 40 protein coding genes (PCGs), 3 rRNA genes, and 22 tRNA genes. The frequent recombination of mitogenome is driven by the non-tandem repetitive sequences. Genome comparison showed that the content of non-tandem repeats in the mitogenome of the algae-like C. demersum was significantly higher than that in terrestrial angiosperms. In monocotyledonous and dicotyledonous plants, there is a significant loss of large ribosomal and small subunit genes. By contrast, C. demersum possesses all 24 core PCGs and inherits a similar number of PCGs as the ancient angiosperms of Magnoliaceae and Chloranthaceae, with only three variable PCGs (rpl6, rps8, and rps19) lost during evolution, suggesting a special evolutionary position of C. demersum in angiosperms. Phylogenetic analyses support the monophyly of Ceratophyllales and Chloranthales and places this clade as sister to a combined monocot–eudicot group. These findings offer new insights and propose alternative hypotheses for reconstructing the early evolutionary history of angiosperms.